Diagnosis of Tobacco Plant Pests and Diseases Using the Forward Chaining Method - Mauladi, Kemal Farouq; Laksono, Arief Budi; Marjudi, Suziyanti Binti (LPPM Telkom University Surabaya, 2025)
Tobacco is a plantation commodity that is susceptible to pests and diseases, such as Phytophthora nicotianae (lanas disease), Myzus persicae (aphids), or Cercospora nicotianae (leaf spots). Lack of farmer knowledge in identifying early symptoms often leads to inappropriate handling and economic losses. This study aims to develop an expert system based on the Forward Chaining method to diagnose tobacco plant pests and diseases quickly and accurately. Symptom data are collected through field observations and literature and then represented as rule-based knowledge (for example,